Development of Integrated Comic Learning Media with Islamic Values - Usman, Yessy -; Purwanto, Hadi; Minarti, Agus; Robiah, Siti (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
This research aims to determine the quality and feasibility of comics as a learning medium using research and development methods with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research instruments included validation questionnaires measuring students' and teachers' interest in the developed product. The product was validated by three experts: a material expert with a score of 94%, a media expert with 83%, and a religious expert with 95%. All three validation results fall under the